PRAJURIT WANITA JAWA DALAM ISTANA MANGKUNEGARA I SURAKARTA - Fika Hidayani (MUWAZAH : jurnal kajian gender, 2013)
The discovery of an ancient manuscript with the title Koninklijk Instituut vor Taal, Land-en Volkenkunde Oriental (KITLV Or) was a very significant discovery, because it can be revised the status of women in ancient times. Previously, women were seen as a restrained and restricted, so their figures were known as the housewives and being satisfied the sexual needs of men. However, with the script KITLV Or, suggested that women in ancient times had played an important role in the government as female bodyguards of King Mangkunagara I and they also followed a country's political development.